The Association between Advanced Maternal Age and Stillbirth Risk - نعيسة ثورة; يوسف أحمد; الفضل آمنة (Latakia University Journal -Medical Sciences Series, 2021)
Background: The number of women who delay childbirth to their late 30s and beyond has increased significantly over the past several decades. Objective: The aim of the study was to evaluate the association between fetal stillbirth and advanced maternal age. Materials and Methods: This prospective observational descriptive study analyzed a total of 1560 singleton gestations without reported congenital anomalies admitted to the Department of Obstetrics and Gynecology in Tishreen university Hospital, Lattakia, Syria, during the period between November 2019 and November 2020. Hazard rates (risk) of stillbirth (fetal death 28 weeks or longer) were calculated for maternal age, parity, medical conditions, pregnancy complications, smoking and neonate gender. Results: The overall rate of stillbirth was 20.5 per 1000 total births (32 stillbirth out of 1560 deliveries). Maternal age was a significant independent risk factor for stillbirth (35 – 39 years HR 2.01), (≥ 40 years HR 2.73). Other significant risk factors were smoking (HR 2.46), nulliparity (HR 3.61), pre-existing hypertension (HR 2.87), and pre-existing diabetes (HR 4.6). The relationship with maternal age for increased antepartum stillbirth risk was seen for both nulliparous and multiparous women but with slightly larger effect sizes in the nulliparous women. Conclusion: Women aged 35 or older in a first pregnancy should be counseled regarding stillbirth risk to assist with informed decision making regarding delivery.